Attachments - Rowell, Rainbow (Plume, an imprint of Penguin Random House, 2012)
"'Hi, I'm the guy who reads your e-mail, and also, I love you ... ' Beth Fremont and Jennifer Scribner-Snyder know that somebody is monitoring their work e-mail. (Everybody in the newsroom knows. It's company policy.) But they can't quite bring themselves to take it seriously. They go on sending each other endless and endlessly hilarious e-mails, discussing every aspect of their personal lives. Meanwhile, Lincoln O'Neill can't believe this is his job now--reading other people's e-mail. When he applied to be 'internet security officer, ' he pictured himself building firewalls and crushing hackers--not writing up a report every time a sports reporter forwards a dirty joke. When Lincoln comes across Beth's and Jennifer's messages, he knows he should turn them in. But he can't help being entertained-and captivated-by their stories. By the time Lincoln realizes he's falling for Beth, it's way too late to introduce himself. What would he say ...?"